Knowing the Day, Knowing the World : Engaging Amerindian Thought in Public Archaeology - Green, Lesley, 1967- (Book collections on Project MUSE., 2013)
Based on more than a decade of research in Palikur lands known as Arukwa in the state of Amapá, Brazil, this book demonstrates both the challenges of comprehending alternative cosmologies and the rich rewards of grappling with Amerindian ways of thinking and knowing. -- Provided by publisher.